6-Hydroxy-5-nitrobenzo[d]oxazol-2(3H)-one - A Degradable Derivative of Natural 6-Hydroxybenzoxazolin-2(3H)-one produced by Pantoea ananatis. Issue 3 (4th May 2017) - Schulz, Margot; Sicker, Dieter; Schackow, Oliver; Hennig, Lothar; Hofmann, Diana; Disko, Ulrich; Ventura, Marina; Basyuk, Kateryna
ABSTRACT: Pantoea ananatis is a bacterium associated with other microorganisms on Abutilon theophrasti Medik. roots. It converts 6-hydroxybenzoxazolin-2(3 H )-one (BOA-6-OH), a hydroxylated derivative of the allelochemical benzoxazolin-2(3 H )-one, into 6-hydroxy-5-nitrobenzo[ d ]oxazol-2(3 H )-one. The compound was identified by NMR and mass spectrometric methods. In vitro synthesis succeeded with Pantoea protein, with isolated proteins from the Abutilon root surface or with horseradish peroxidase in the presence of nitrite and H2 O2 . Nitro-BOA-6-OH is completely degraded further by Pantoea ananatis and Abutilon root surface proteins. Under laboratory conditions, 6-hydroxy-5-nitrobenzo[ d ]oxazol-2(3 H )-one inhibits Lepidium sativum seedling growth whereas Abutilon theophrasti is much less affected. Although biodegradable, an agricultural use of 6-hydroxy-5-nitrobenzo[ d ]oxazol-2(3 H )-one is undesirable because of the high toxicity of nitro aromatic compounds to mammals.